Sex differences in hospital outcomes of medically-managed type B aortic dissection - Luna, Paulina; Amil, Faris; Roman, Mary J.; Singh, Nickpreet; Iranitalab, Teagan; Cheung, Jim W.; Yeo, Ilhwan; Devereux, Richard B.; Weinsaft, Jonathan; Girardi, Leonard; Mecklai, Alicia; Ascunce, Rebecca; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMedical management is recommended for uncomplicated type B aortic dissection (TBAD). However, data focused on sex differences in outcomes in TBAD patients managed medically are limited.MethodsHospitalizations of adults with TBAD were identified using the 2016–2019 Nationwide Readmissions Database. TBAD diagnosis was deduced by inclusion of thoracic or thoracoabdominal aorta dissection and exclusion of presumed type A aortic dissection. Hospitalizations associated with intervention were excluded. Multivariable logistic regression modeling was used to investigate the association of sex with in-hospital mortality. A Cox proportional hazards model was used to assess the association between sex and readmission rates.ResultsThere were 52,269 TBAD hospitalizations (58% male). Compared to men, women were older (72 vs. 65 years), had higher in-hospital mortality (11.5% vs. 8.5%), shorter median length of stay (3.95 vs. 4.23 days), and lower rates of elective admissions (6.4% vs. 8.2%) (all p < 0.05). Despite similar rates of hypertension, lower rates of coronary artery disease and smoking, and decreased rates of hospital-related complications, women experienced increased adjusted in-hospital mortality (odds ratio: 1.16; 95% CI, 1.06–1.27). There were no sex differences in readmission risk at 30, 90, and 180 days.ConclusionsWomen with TBAD managed medically experienced higher in-hospital mortality than men despite lower rates of atherosclerotic disease and risk factors. However, there were no sex differences in readmission risk at 30, 90, and 180 days. Prior research has demonstrated sex differences in presenting TBAD characteristics, including older age, varied signs/symptoms, and diagnostic delay in women. Data are needed to delineate additional causes of adverse acute outcomes in women managed medically, including condition- and medication-specific factors.